Women in dialogues : (m)uses of culture - Direnç, Dilek; İşçi, Günseli Sönmez; Kolinská, Klára (Cambridge Scholars Pub., 2008)
Women in Dialogue: (M)Uses of Culture results from an international symposium held at Ege University, Izmir, Turkey, in 2006, which brought together scholars from over ten countries, and from multiple academic backgrounds, who share professional interest in women's studies, and, to no less degree, in current women's realities. The book presents a collection of essays united by a common focus on the position of women as objects of cultural production in different geographic, national, and poli ...